Elevated CO2 influences nematode-induced defense responses of tomato genotypes differing in the JA pathway. - Yucheng Sun (Public Library of Science (PLoS), 2011)
Rising atmospheric CO(2) concentrations can affect the induced defense of plants against chewing herbivores but little is known about whether elevated CO(2) can change the induced defense of plants against parasitic nematodes. This study examined the interactions between the root-knot nematode Meloidogyne incognita and three isogenic tomato (Lycopersicon esculentum) genotypes grown under ambient (390 ppm) and elevated (750 ppm) CO(2) in growth chambers. In a previous study with open-top chambers in the field, we reported that elevated CO(2) increased the number of nematode-induced root galls in a JA-defense-dominated genotype but not in a wild-type or JA-defense-recessive genotype. In the current study, we tested the hypothesis that elevated CO(2) will favor the salicylic acid (SA)-pathway defense but repress the jasmonic acid (JA)-pathway defense of plants against plant-parasitic nematodes. Our data showed that elevated CO(2) reduced the JA-pathway defense against M. incognita in the wild-type and in a genotype in which defense is dominated by the JA pathway (a JA-defense-dominated genotype) but up-regulated the SA-pathway defense in the wild type and in a JA-defense-recessive genotype (jasmonate-deficient mutant). Our results suggest that, in terms of defense genes, secondary metabolites, and volatile organic compounds, induced defense of nematode-infected plants could be affected by elevated CO(2), and that CO(2)-induced changes of plant resistance may lead to genotype-specific responses of plants to nematodes under elevated CO(2). The changes in resistance against nematodes, however, were small relative to those reported for chewing insects.